Insights into the association of Nicotiana tabacum health with eukaryotic microbial community and environmental factors - Chai, Longxin; Shun, Yue; Xue, Lei; Yang, Yong; Li, Mei (Frontiers in Plant Science, 2025)
As an important cash crop, Nicotiana tabacum’s yield and quality are influenced by various factors, yet the correlations between its health status, microbial community, and environmental factors remain largely unexplored. In this study, we analyzed the microbial diversity of Nicotiana tabacum rhizosphere microbiomes using ITS rDNA sequencing under different conditions. Compared with soil associated with healthy Nicotiana tabacum, the alpha and beta diversity of the eukaryotic microbial community decreased in soil with diseased Nicotiana tabacum, indicating a decline in microbial abundance and composition. Compared with healthy soil, the eukaryotic microbial community in diseased soil exhibited looser structural networks, with the assembly process of both communities predominantly governed by stochastic processes. Soil element measurements and correlation analyses identified pH, manganese, and copper as key environmental factors associated with the health status of Nicotiana tabacum. A machine learning model incorporating environmental factors and major microbial phyla was developed to predict Nicotiana tabacum health status, achieving a high accuracy of 93%. These findings collectively offer comprehensive insights into the relationship between Nicotiana tabacum health status, soil conditions, environmental factors, and eukaryotic microbial community.